Apiculture commodity development in Goma District: experiences from IPMS - Baredo, Y.; Hoekstra, Dirk; Berhe, Kahsay (International Livestock Research Institute, 2010)
Goma is endowed with different flora and adequate moisture which favors honey production. As a result, bee farmers started producing honey since time immemorial using traditional hives, mostly made of bamboo. Improved hive production in the Woreda started in 1987 among cooperatives formed during the military regime. In 2007, apiculture was identified as one of the priority commodity for Goma PLW through participatory priority commodities identification. Major constraints identified were shortage and/or substandard inputs supply, poor quality honey, lack of market, skill and knowledge limitations of bee farmers and technical staff. To address the challenges, value-chain development approach was exercised and in this regard the following developments were recorded. One interested honey shop was upgraded to become an apiculture input shop in Agaro town with financial assistance from OCSSCo/IPMS and technical assistance from the District Livestock Development and Production Agency (LDPA) and IPMS. This input shop supplied considerable inputs to bee farmers who also provide commercial services for their neighbours. One of the important inputs delivered to bee farmers was imported honey extractor but less demand was observed due to its high price. Moreover, one interested honey producers association named Wojin Gudina Honey Producers Association was formed and got legal identity. The association is expected to play market regulatory role, quality assurance, do bulking of member produce as well as non members to maintain bargaining power. About 44 interested farmers and 12 technical staff received skill and knowledge upgrading training and in this regard Jima University (JU) played a big role. More focus was given to transforming traditional to transitional hives (Kenya Top Bar), which was a change for the frame hives (modern hives) which had been introduced before. Twenty interested farmers received 123 transitional hives in Acha Afeta PA through credit and also transitional hive use has shown significant increase within and outside interested farmers in the last two years. To address market constraints, an effort was made to link honey producer with honey processing and export enterprises and in this regard Beza Mar honey processing and exporting enterprise has already started the process to buy Goma honey. Prior to this, an attempt was also made with another commercial processor but was not successful. The effects of various interventions are just emerging and are expected to come to full fruition over time. A household (HH) survey conducted by the project indicated however that adopters of improved apiculture technologies produced in 2008, on average, about birr 3,400 of honey per year compared to birr 225 by traditional bee keepers. Major lessons learned include that the intervention stimulated increased demand for improved hives and better use of existing hives. As compared to other Districts, involvement of private sector in the sale of accessories for improved bee hives and honey processing is emerging. Most of the honey produced from framed hives is extracted using locally made crude extractors with less or no food graded approval and also less quality honey. These extractors are operated commercially by private individuals, but require further technical support to improve quality. The development of a quality honey market is just emerging, however as indicated in the prices, no clear price incentive for quality honey is observed yet, probably because of the still relatively small volume entering into this market segment. Another indication of the still limited demand for clear honey is the increase in the numbers of traditional hives in the last two to three years.